The Effect of Motivation, Ethics, and Work Discipline on Performance of Employees at the Kotapinang Regional General Hospital, South Labuhanbatu - Nurmiah Harahap; Ade Parlaungan Nasution; Azidin Harahap (Quantitative Economics and Management Studies, 2022)
Purpose from study sees Influence motivation, ethics and discipline work to performance employee hospital of kotapinang. Researched data with spread questionnaire for 100 research samples, namely employees General Hospital of Penang. For see results analysis with use application that is spss. Test conducted by partial and simultaneous with To do a t-test, regression f test and also see determination. t test results motivation has a positive and significant effect on performance, it can be seen from the results of the t-table test which shows that 2.892> 1.984 (t-count > t-table), ethics has a positive and significant effect on performance, it can be seen from the results of the t-table test which shows that 3.038> 1.984 (t-count > t-table), discipline work does not have a positive and significant effect on performance, it can be seen from the results of the t table test which shows that -0.055 < 1.984 (t-count < t-table), results testing by simultaneous show that motivation, ethics and discipline work give positive and significant influence _ to performance Thing this seen from F count > F table (9,358 > 2.47).